Philosophy to Strengthen Baitul Maal wat Tamwil Law in Indonesia - Erisa Ardika Prasada; Joni Emirzon; KN. Sofyan Hasan (Sriwijaya Law Review, 2020)
Baitul Maal wat Tamwil (BMT) is a non bank financial institution that operates based on sharia principles. As an alternative financial institution, BMT can support the acceleration of national economic growth, but BMT was established and developed with a gradual process of legal legality. BMT status is determined by the number of assets owned, the BMT has a different legal status according to the stages of the number of assets, and is subject to various and partial laws in accordance with the stage of legal status. The purpose of writing is to explain the philosophical basis of the need for legal entities and the formulation of legal norms of BMT as a legal strengthening of populist economic institutions in Indonesia. This type of legal research is normative legal research on legal principles and legal systematics. Based on the discussion it was concluded that the philosophical basis of the need for legal entities and the formulation of legal norms regarding BMT in Indonesia as a legal strengthening is for legal certainty so that can provide recognition, protection, and facilities for the development and benefits of BMTs for micro and small entrepreneurs who do not receive financing services from bank financial institution.